Does COVID-19 Pandemic Impact on China’s Economy Structure and Sustainability of Deep Economic Determinants? - Long, Hai; Li, Wenwei (International Journal of Economics and Financial Issues, 2021)
The outbreak of COVID-19 has impacted on the global economy since 2020. This paper employs regression models to investigate China’s economy structure and sustainability of deep determinants, such as human capital, business environment. It finds that the central government like to adjust China’s economy structure to mitigate the impact of crucial crisis to remain economic sustainability. Additionally, COVID-19 like SARS has no impact on Chinese economic sustainability, because this pandemic is unable to effect economic deep determinants in the short run. Human capital accumulation is the significant deep factors, and COVID-19 epidemic has no impact on these long-run factors during a short period. It suggests further human capital including labor quantity and education is currently the most significant determinants for China’s economy sustainability, followed by the upgrading business environment. Keywords: COVID-19, Economy structure, Deep determinants, Economic Sustainability JEL Classifications: O11, O40, O53 DOI: https://doi.org/10.32479/ijefi.11263